PELATIHAN PEMBUATAN TUNGKU KRUSIBEL UNTUK PENGECORAN LOGAM BAGI MAHASISWA TEKNIK MESIN UM PONTIANAK - - Aspiyansyah; - Gunarto (Universitas Muhammadiyah Pontianak, 2017)
The purpose of this community service was to train students of University of Muhammadiyah Pontianak in constructing crucible as metal melting instrument. Crucible stove can be used both in experiment classes and in researches. The program included preparation, instrument manufacturing, training, and reporting. As the program ended, a crucible has been manufactured and used as instructional media in metal casting class. Keywords: crucible stove, casting, metal, training